Exploring mobile social media advertising towards purchase intention: the roles of Ducoffe’s web advertising model, credibility, and incentives - Chan, Wen Shen; Chang, Yong Chee; Ooi, Joshua Jun Ern; Kok, Ming Yenn; Yip, Khong Chen (2019)
With the proliferation of mobile social media users, mobile social media advertising (mobile SMA) have become among the most widely used promotional media among marketers. This paper provides theories that will further explain the determinants of mobile SMA which will affect consumers’ purchase intention. The Web Advertising Model introduced by Ducoffe (1995) has been adopted as the framework for this research. The adopted model by Ducoffe (1995) for this study has been expanded to consider two more additional variables which are credibility from Mackenzie & Lutz (1989) and incentives from Varnali, Yil & Toker (2012). The variables proposed to determine the purchase intention of consumers towards mobile SMA are Informativeness, ntertainment and Irritation which are the original components of the Web Advertising Model, while credibility and incentives are the additional proposed variables. A total of 280 survey questionnaires have been collected from mobile social media users in the 5 major states of Malaysia. Advertisers are able to retrieve valuable insights of the effects and causes of consumer purchase intention towards mobile SMA. The techniques used in the data analysis for our study are reliability test, earson correlation test, together with multiple regression analysis. Based on the outcomes obtained, every variables are proved to be significantly related to the consumers’ purchase intention towards mobile SMA. Incentives has the strongest significance for purchase intention of consumers towards mobile SMA.